Regional Anaesthesia for the Neonate - Bharti Wadhwa; Neha Hasija; Kirti N Saxena (EL-Med-Pub, 2017)
Numerous regional and local anaesthesia techniques are available for safe use in neonates and can be administered either in combination with general anesthesia or in the awake neonate. Regional anaesthesia provides effective analgesia with reduced drug requirement which is especially beneficial in view of the immature physiology and metabolism in the neonate. The reduced requirement of anaesthetic drugs facilitates stable hemodynamics, faster recovery and a decreased length of stay in the neonatal intensive care unit.